Age-related changes in sperm DNA methylation and their forensic and clinical implications - Kotková, Lucie; Drábek, Jiří (Epigenomics, 2023)
As a link between a stable genome and a dynamic environment, epigenetics is a promising tool for mapping age-related changes in human DNA. Methylated cytosine changes at specific loci are generally less studied in sperm DNA than in somatic cell DNA. Age-related methylation changes can be connected to various reproductive health problems and multiple disorders in offspring. In addition, they can be helpful in forensic fields, where testing of specific loci in semen samples found at sexual assault crime scenes can predict a perpetrator's age and narrow down the police investigation. This review focuses on age-related methylation changes in sperm. It covers the biological role of methylation, methylation testing techniques and the implications of methylation changes in forensics and clinical practice.
Keywords: semen; spermie; Semen; Spermatozoa; DNA; lidé; metylace DNA; sperm; sperma; methylation; epigeneze genetická; age prediction; forensic phenotyping; Male; DNA Methylation; epigenome; mužské pohlaví; Epigenesis, Genetic; Humans